2019
DOI: 10.1177/0306624x19866115
|View full text |Cite
|
Sign up to set email alerts
|

Examining Recidivism in a Prostitution Diversion Program

Abstract: Street-based sex work is criminalized throughout much of the U.S. Diversion programs have shown mixed results. This study examined the effect a quasi-experimental intervention (prostitution diversion program, n = 149) had on prostitution rearrest compared with a waitlist control group ( n = 77) among N = 226 individuals arrested for prostitution in Baltimore. In both groups, n = 64 (28.32%) were rearrested for prostitution over 30 months. Tests of differences compared groups with a significant difference in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The program included case management and counseling services, as well as drug testing. Enrollees who attended required meetings and supplied drug‐negative urine samples “graduated” the program, were free of further criminal justice consequences related to the charge, and were eligible to have their charge expunged (Koegler et al., 2020; Shdaimah, 2010). To be included in the present study, participants were required to be enrolled in medication‐assisted treatment (i.e., methadone or buprenorphine) for the treatment of opioid use disorder and referred to the study by social workers employed by the Baltimore City State's Attorneys' Office.…”
Section: Methodsmentioning
confidence: 99%
“…The program included case management and counseling services, as well as drug testing. Enrollees who attended required meetings and supplied drug‐negative urine samples “graduated” the program, were free of further criminal justice consequences related to the charge, and were eligible to have their charge expunged (Koegler et al., 2020; Shdaimah, 2010). To be included in the present study, participants were required to be enrolled in medication‐assisted treatment (i.e., methadone or buprenorphine) for the treatment of opioid use disorder and referred to the study by social workers employed by the Baltimore City State's Attorneys' Office.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning Western exit programmes, Wilson et al (2015) found that the methods applied to help the sex workers typically revolve around individual peer‐support, behaviour modification, and trauma support. In the USA, researchers have questioned the efficiency of the exit programmes (Koegler et al, 2020; Roe‐Sepowitz et al, 2011; Wahab, 2006) and the use of coercive and disempowering approaches against sex workers (Wahab & Panichelli, 2013). In the UK, researchers found that the exit programmes tended to individualise the problems of the sex workers (e.g., Carline & Scoular, 2015) at the same time as the programmes tended to offer insufficient help and support to find other sources of income (Scoular & O'Neill, 2007).…”
Section: Earlier Research On Exit Programmesmentioning
confidence: 99%
“…In addition, sex worker participants frequently report that they will continue trading sex, and research has shown that PDPs fail to curb recidivism, which means that PDPs do not achieve the criminal legal system's objectives (Koegler et al, 2019; Wahab, 2006). Some participants name the harmful ideology that underlies therapeutic intervention and mandated treatment more generally: workers consider these women troubled, pathological, or “fallen” and believe they must be “cleaned up” (Wahab, 2006, p. 79).…”
Section: Sex Work Interventions Across Timementioning
confidence: 99%